2021
DOI: 10.1159/000512779
|View full text |Cite
|
Sign up to set email alerts
|

Acute Mesenteric Infarction: The Chameleon of Acute Abdomen Evaluating the Quality of the Diagnostic Parameters in Acute Mesenteric Ischemia

Abstract: <b><i>Introduction/Objective:</i></b> Acute mesenteric ischemia (AMI) is difficult to diagnose. Since the established parameters have low sensitivity and specificity, the aim of this study is to analyze the diagnostic quality of the established parameters of AMI. <b><i>Methods:</i></b> All patients that underwent emergency surgery due to suspected diagnosis of mesenteric ischemia at the University Medical Center Hamburg-Eppendorf between 2008 and 2014 were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…They also reported that the odds ratios were 7.57 and 5.04 in predicting intestinal necrosis when the neutrophil-lymphocyte ratio was >11.05 and the platelet-lymphocyte ratio was >156.26. However, other studies did not find that WBC or CRP were risk factors associated with intestinal necrosis [18‒20]. In AMI cases, intestinal hypoxia leads to increased anaerobic glycolysis and lactate metabolites, which eventually leads to metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that the odds ratios were 7.57 and 5.04 in predicting intestinal necrosis when the neutrophil-lymphocyte ratio was >11.05 and the platelet-lymphocyte ratio was >156.26. However, other studies did not find that WBC or CRP were risk factors associated with intestinal necrosis [18‒20]. In AMI cases, intestinal hypoxia leads to increased anaerobic glycolysis and lactate metabolites, which eventually leads to metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…In AMI cases, intestinal hypoxia leads to increased anaerobic glycolysis and lactate metabolites, which eventually leads to metabolic acidosis. Therefore, many studies have reported that pH and lactate are risk factors associated with intestinal necrosis [ 16 , 17 , 19 , 21 ]. The guidelines suggest that laparotomy should be performed in patients with peritonitis due to the high possibility of bowel necrosis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%